The Utility of Serial Echocardiography Parameters in Management of Newborns with Congenital Diaphragmatic Hernia (CDH) and Predictors of Mortality - Roopali Soni (14146686) (2022)
Ventricular dysfunction may be found in 40% of newborns with CDH, and is not only a predictor of disease severity, but also mortality and need for ECMO. We conducted this study to assess the utility of serial echocardiography in management of newborns with CDH and their survival outcomes. This is a retrospective study, wherein the demographic, clinical and echocardiographic data from our local CDH registry and hospital clinical database were analyzed to study the correlation of timed echocardiographic findings with mortality and other outcomes. Fourty-two newborns with CDH were admitted during the study period (M/F:19/23), with median gestation of 38 weeks (IQR:36–39) and birth weight of 2.83 kg (IQR 2.45–3.17). Thirty-one were left-sided, seven right, one central, and three bilateral hernias. Twelve infants (28%) died in early infancy. Three infants were excluded from analysis due to either palliation at birth or significant cardiac anomaly. A total of 137 echos from 39 infants were analyzed. Seventy percent of newborns who died and had an echo within the first 72 h, were noted to have suffered from moderate to severe PH. Birth weight < 2.8 kg, RVSP > 45.5 in the first 72 h and postoperative VIS > 23.5 and RSS > 4.3 were good predictors of mortality. Markers of elevated pulmonary pressures and cardiac function were useful in guiding therapy. Serial timed functional echocardiography (f-Echo) monitoring allows targeted therapy of patients with CDH. Birth weight, initial severity of pulmonary hypertension and postoperative RSS and VIS may be useful in predicting mortality. Other Information Published in: Pediatric Cardiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00246-022-03002-y